China’s String Of Pearls: Security Implications For India - Ul Ain, Qurat; Ahmad Bhat, Mukhtar (International Journal of Psychosocial Rehabilitation, 2020)
China is emerging the great power of 21st century Ports and pipelines become veins and capillaries for the survival of great nations. China since 1990s has encapsulated an Idea under which it persuaded the South Asian Nations Myanmar, Bangladesh, Sri Lanka, Maldives and Pakistan to allow its ports used by China for military purposes or to allow construct naval bases. This process of persuasion is popularly known as Chinese strategy of String of Pearls. The String of Pearls is a network of installations the aim of which is to prove its power in Indian Ocean, the backyard of India. The String of Pearls extends from the coast of mainland China to the port of Sudan. It is said by Ms Cristina Lin who is an energy security consultant and former director for China affairs in policy planning at US department of defence said dragon will become a great sea power in 21st century, and that it may challenge the predominance of United States in the Indian ocean and could threaten India in their very own Bay of Bengal. India considers it as a security threat responding it by upgrading its naval power and isiinvolving great powers like US and France by signing a strategic pact to thwart Beijing, s expansion into India’s traditional sphere of influence. The research paper will Analyse the political strategies related to String of Pearls and objective of this Chinese Foreign policy. The paper will also explore the security concerns that it poses for the regional powers particularly India. It will also analyze the security implications that the India have Vis-a-Vis encirclement and its impact on Indian security. Both descriptive and analytical method will be used.